Cloning and Characterization of a Somatic Embryogenesis Receptor-Like Kinase Gene in Cotton (Gossypium hirsutum) - Ya-li SHI; Rui ZHANG; Xiao-ping WU; Zhi-gang MENG; San-dui GUO (Journal of Integrative Agriculture, 2012)
A novel gene, GhSERK1, was identified in cotton. It encoded a protein belonging to the somatic embryogenesis receptorlike kinase (SERK) family. The genomic sequence of GhSERK1 was 6920 bp in length, containing a predicted transcriptional start site (TSS). Its full-length cDNA was 2502 bp, encoding a protein of 627 amino acids. Sequence analysis of GhSERK1 revealed high levels of similarity to other reported SERKs, as well as a conserved intron/exon structure that was unique to members of the SERK family. Expression analysis showed that GhSERK1 mRNA was present in all organs of cotton plants and at different developmental stages, but its transcripts were most abundant in reproductive organs. Compared with that of the male-fertile line, the level of GhSERK1 mRNA was lower in the anther of the male-sterile cotton line, in which the pollen development was defected. Taken together, these findings illustrated that the GhSERK1 play a critical role during the anther formation, and may also have a broad role in other aspects of plant development.